2017
DOI: 10.1039/c7tc04194b
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the spin transition properties of iron-triazole coordination polymers within silica-based nanocomposites

Abstract: Preserving the spin transition properties of iron-triazole coordination polymers within silica-based nanocomposites †T. Coradin * a and C. Roux* a One dimensional iron(II) coordination polymers formed from 1,2,4-triazole bridging ligands are a unique class of spin-crossover materials (SCO). The integration of those coordination polymers into devices for practical applications remains a major challenge. Using a nanocomposite approach based on the control of coordination polymer interactions with chemically engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 60 publications
0
22
1
Order By: Relevance
“…We have shown that the presence of NPs and the subtle balance between the three interacting components is a unique way to control the SCO properties of the gel. 36 In this case, transition temperatures (heating T ↗ and cooling T ↘ ) have been shown to increase with increasing SiO 2 content ( Fig. S1 and S2 †).…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…We have shown that the presence of NPs and the subtle balance between the three interacting components is a unique way to control the SCO properties of the gel. 36 In this case, transition temperatures (heating T ↗ and cooling T ↘ ) have been shown to increase with increasing SiO 2 content ( Fig. S1 and S2 †).…”
Section: Introductionmentioning
confidence: 75%
“…Sulfonate functionalization of the surface proceeded through a previously described two-step procedure. 36 Zeta potential and size distribution are systematically measured using a Malvern Zetasizer Nano ZS90 instrument giving a negative zeta potential of ca. −53 mV in 0.5 M acetic acid ( pH 2.5) and a hydrodynamic diameter of ca.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
See 3 more Smart Citations